Family Disorganization in Short Stories by Female Writers on the WebsiteBasabasi.co - Ramdhani, Marlinda; Wahyuni, Wika (JUPE : Jurnal Pendidikan Mandala, 2025)
Social problems that are often raised by female writers in literary works tend to be diverse. However, one of the social problems that often appears in literary works by female writers is the problem of family disorganization. This study aims to describe the problem of family disorganization in short stories by female writers on the Basabasi.co site. This study is classified as a descriptive qualitative research type with a sociology of literature approach. The data for this study are sentences or paragraphs that contain the problem of family disorganization in short stories. The data sources for this study were eight short stories by female writers that raised the problem of family disorganization and were published throughout 2024 on the Basabasi.co site. The method of collecting research data used literature studies. The results of the study showed that there were 10 indicators of family disorganization found, namely unclear roles in the family, poor communication, conflict between family members, lack of emotional attachment, inability to make joint decisions, violence in the family, disharmony in parent-child relationships, deviant behavior in the family, and unstable economic conditions.